ChemInform Abstract: A Strecker Approach to 2‐Substituted Ethyl 5‐Aminothiazole‐4‐carboxylates. Issue 32 (22nd July 2016) - Cheng, Ken; McClory, Andrew; Walker, Whitney; Xu, Jie; Zhang, Haiming; Angelaud, Remy; Gosselin, Francis
Abstract: The three step sequence for the synthesis of the title thiazoles involves the 1, 2‐addition of thioamides to glyoxylate (II), the treatment with acetyl chloride, and finally the Strecker addition‐cyclization reaction of the resulting imine precursors.